Analisis Pengukuran Produktivitas Menggunakan Metode Marvin E. Mundel - Suparno Suparno; Nur Hamidah (Universitas Katolik Parahyangan, 2019)
Competition in many companies can be measured by the level of productivity of the company. CV. Gavra Perkasa Gresik is a manufacturing company engaged in the wood processing industry, among the products produced is turning. So far, the company has never made productivity measurements so that, if output is low, the company thinks it is not good without analyzing the causes specifically and not paying attention to the efficiency of the use of resources (inputs) that are owned. Productivity measurement to find out how the condition of the company's productivity, whether experiencing an increase or decrease, is necessary to measure productivity using the model Marvin E. Mundel. This measurement is carried out on labor input, material, energy, capital and total input. The data needed for productivity analysis is taken from 2016 as the base period and 2017 as the measurement period. The results of calculation of productivity using the mundel model not all inputs have decreased, causing the company's total productivity to be 98.18% which has a good impact on the company. Keywords: Productivity, CV. Gavra Perkasa, Turning, Marvin E. Mundel